Assembly rules of ectoparasite communities across scales: combining patterns of abiotic factors, host composition, geographic space, phylogeny and traits. Issue 2 (14th July 2014) - Krasnov, Boris R.; Shenbrot, Georgy I.; Khokhlova, Irina S.; Stanko, Michal; Morand, Serge; Mouillot, David
<x xml:space="preserve">Abstract</x> We investigated the role of environmental filtering as an underlying mechanism of assembly of compound communities of fleas parasitic on Palearctic small mammals at two spatial scales; a continental scale (encompassing regions across the entire Palearctic) and a regional scale (across sampling localities within Slovakia). We used the three‐table ordination (the RLQ analysis) and its extended version that links species occurrences with geographic space, environmental variables, and species traits and phylogeny (the ESLTP analysis). We asked whether environmental filtering acts as an assembly rule of compound communities of fleas and, if yes, a) whether the effect of environment on species composition of compound communities of fleas differs between spatial scales and b) what are the relative importance of the abiotic and host environments. We found that compound communities of fleas are, to a great extent, assembled via environmental filters that represent interplay between filtering via abiotic environment and filtering via host composition. The relative importance of these two components of environmental filtering differed between spatial scales. Host composition had a stronger effect on flea assembly than abiotic environment on the continental scale, while the opposite was true for the regional scale. The likely reason behind this scale‐dependence is that communities on the regional scale are mainly governed by ecological and epidemiological processes, while communities on the continental scale are mainly affected by evolutionary, biogeographic and historical forces.